The Relationship of Self-Management with Quality Lives of Hypertension Patients - Linda Marni; Armaita; Yesi Maifita; Elza Safitri (Jurnal Penelitian Pendidikan IPA, 2024)
Hypertension is one of the non-communicable diseases that can cause death. This disease is categorized as a silent disease because people with hypertension do not know they have hypertension before checking their blood pressure. Nationally population prevalence of Indonesia with high blood pressure reaches 34.11% of Indonesia's total population of 270.20 million people. The purpose of the study was to determine the relationship between self-management and the quality of life of people with hypertension in the Working Area of the Pariaman Health Center in Pariaman City in 2023. Type of analytical descriptive research with a research design using a cross-sectional approach. This research was conducted in the working area of the Pariaman Health Center in Pariaman City in 2023. The population in this study was 5337 people, while the sample taken was 44 people from September 20 to October 6, 2023. Sampling through Purposive Sampling. Statistical tests using univariate analysis and bivariate analysis using Chi-Square. The results of the study show Most of the people with hypertension (50.0) have poor Self Management in overcoming the problem of hypertension, and Most of the people with hypertension (50) have a poor quality of life. There is a significant relationship between Self-Management and the Quality of Life of Hypertensive Patients in the Working Area of the Pariaman Health Center in Pariaman City in 2023 (p-value = 0.000 < 0.05). Respondents should pay more attention to the food consumed, exercise, or activities that are useful to improve heart performance, reduce smoking habits that can cause decreased blood flow to various organs, and improve heart performance.